THE EPIC "QIRIQ QIZ" AND ITS UNIQUE FEATURES IN THE REPERTAURES OF JRAVS - Zaripova, Zulfiya Sarsenbaevna (SCIENCE and SOCIETY, 2026)
The article discusses the epic poem "Qiriq qiz" which is part of the oral tradition of the Karakalpak people. The recording of the dastan, its periods of origin, performers, compositional structure, and scientific and practical works on this topic are presented.